2004
DOI: 10.1007/bf03166454
|View full text |Cite
|
Sign up to set email alerts
|

Role of admixtures on dissociation of molecular gases

Abstract: It is known that dissociation degree in the afterglow can be increased substantially if a small admixture is added to to the main gas prior to its passage through the discharge. In this experimental work we measured the influence of the admixture on dissociation degree, when it is added directly into the afterglow. : 52.70.Gw, 82.33.Xj PACS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…For example, Kudrle et al reported an approximately 60-fold enhancement of N 2 dissociation with the neon admixture. 26) However, in their experiments, the argon admixture showed a greater effect on the N 2 dissociation than the neon admixture in the afterglow region of microwave discharge with a power of 100 W and a pressure of 450 Pa, 26,31) inconsistent with our experimental results for argon-diluted N 2 discharge. They pointed out the essentiality of the surface dissociation mechanism for N 2 dissociation.…”
Section: Dissociation Degree Of Nitrogen Moleculecontrasting
confidence: 94%
“…For example, Kudrle et al reported an approximately 60-fold enhancement of N 2 dissociation with the neon admixture. 26) However, in their experiments, the argon admixture showed a greater effect on the N 2 dissociation than the neon admixture in the afterglow region of microwave discharge with a power of 100 W and a pressure of 450 Pa, 26,31) inconsistent with our experimental results for argon-diluted N 2 discharge. They pointed out the essentiality of the surface dissociation mechanism for N 2 dissociation.…”
Section: Dissociation Degree Of Nitrogen Moleculecontrasting
confidence: 94%
“…Once the new mechanism explaining the increase in N atom after the addition of oxygen into the post-discharge is discovered, the possibility to explain the increase in N when oxygen is added into the discharge itself should be studied. To test whether the observed phenomenon occurs only in a particular gas mixture or the enhanced dissociation after the injection of admixture is rather a general effect, we measured [60,64,65] the dissociation degree in several combinations of main gases and admixtures. The phenomenon was observed for all tested combinations of molecular gases (O 2 into N 2 , N 2 into O 2 , N 2 into H 2 , O 2 into H 2 ).…”
Section: Role Of Admixtures On Dissociationmentioning
confidence: 99%